2020
DOI: 10.1063/5.0000968
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of heat and mass transfer by the interaction of two drops of water of different sizes

Abstract: An interaction of an incident drop on a sessile drop located on a hot wall was experimentally investigated. The behavior of convection with and without graphite particles was studied. Graphite particles lead to a decrease of mass transfer after droplet fall. The falling droplet caused a narrow temporal leap in speed into sessile drop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Wakefield et al 26 also observed these hydrodynamic phenomena between a falling droplet and a sessile droplet and then developed an analytical model to predict the maximum spreading diameter based on the conservation of energy with two treatments of energy dissipation. Glezer and Zhuikov 27 carried out an experiment about an incident drop impacting a sessile drop and analyzed the convection behavior with and without graphite particles. Results showed that the mass transfer decreases with the presence of graphite particles after droplet impact.…”
Section: Introductionmentioning
confidence: 99%
“…Wakefield et al 26 also observed these hydrodynamic phenomena between a falling droplet and a sessile droplet and then developed an analytical model to predict the maximum spreading diameter based on the conservation of energy with two treatments of energy dissipation. Glezer and Zhuikov 27 carried out an experiment about an incident drop impacting a sessile drop and analyzed the convection behavior with and without graphite particles. Results showed that the mass transfer decreases with the presence of graphite particles after droplet impact.…”
Section: Introductionmentioning
confidence: 99%